Analysis of the Distribution and Microscopic Characteristics and Disintegration Characteristics of Carbonaceous Rocks: A Case Study of the Middle Devonian Luofu Formation in Western Guangxi of China. (30th August 2020) - Luo, Junhui; Wu, Yong; Mi, Decai; Ye, Qiongyao; Huang, Haifeng; Chang, Zhenchao; Chen, Qinglin; Zhang, Tao; Sun, Guanhua; Wang, Xueheng; Wang, Yu; Liu, Xianlin
Abstract : Carbonaceous rock is a special soft rock containing TOC organic carbon 6%∼40%. In order to reveal the influence of engineering characteristics of carbonaceous rock on the engineering construction, firstly the stratigraphic distribution of carbonaceous Rocks in Guangxi is investigated, and the genetic mechanism and tectonic environment of carbonaceous rocks are discussed. Secondly, the influence of pore microstructure on the disintegration characteristics of carbonaceous rocks is analyzed. The role of geochemical characteristics of carbonaceous rocks (mineral composition, TOC total organic matter content, and type) on engineering properties is revealed. Finally, combined with the distribution, structure, microstructure, and microscopic characteristics of the previous studies, the disintegration mechanism of carbonaceous rocks in water swelling and heat dehydration is discussed. The results are as follows. (1) Carbonaceous rocks in Guangxi are mainly distributed in Devonian, Carboniferous, and Cambrian systems. It is mainly formed in anoxic and reductive deep water basins, slopes, and relatively confined coastal lagoons and swamps. The carbonaceous rocks in the Devonian Luofu formation are most typical. (2) The pores of carbonaceous rocks are divided into mineral pores, organic matter pores, and microfracture, which are mainly mineral pores. The more developed pores in mineral pores are intragranular dissolved pores. Secondly, mineral intergranular pores and a small amount of intergranular dissolution pores and less inner pores. Organic matter porosity increases with the increase of shale organic carbon content and maturity, but the shale porosity and adsorption capacity decrease when shale maturity reaches more than 2.4%. (3) Clay minerals in carbonaceous shale mainly consist of illite and illite/montmorillonite layer, which have water swelling and heat dehydration. The total average value of TOC (total organic matter content) is more than 1%, which belongs to carbonaceous rocks of medium high grade hydrocarbon source rocks. Organic matter is mainly dominated by type I and II1 -II2 type with large hydrocarbon generating potential, which is prone to oxidation-reduction reaction and cause rock disintegration.